Pendekatan Preventif Maintenance Mesin Conveyor PT. XYZ Guna Menjaga Kinerja Conveyor - Ducha, Moh Syamsi; Kurniawan, Rudi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ is a company engaged in the field of packaged drinking water (AMDK). The system used in this company has a very good system, aimed at meeting consumer demand. The implementation of preventive conveyors is very important to maintain the performance and reliability of the conveyor system in the long term. By taking preventive measures regularly, we can avoid damage and disruptions that can stop production or cause high repair costs. Through preventive maintenance, we can ensure that conveyor components continue to function optimally, reduce the risk of failure, and extend the life of the equipment. Preventive Maintenance is a maintenance and care activity carried out to prevent unexpected damage and find conditions or conditions of the conveyor that are damaged when used.